2007
DOI: 10.1597/05-137
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Status and Oral Hygiene in Two Populations of Cleft Patients

Abstract: The oral hygiene regimens in Germany and Poland were not comparable, as more plaque was found in the Polish than in the German population. Plaque accumulation seems not to be a key factor in causing periodontal destruction in the cleft area. Factors other than oral hygiene should be considered of major importance in relation to the development of gingival recession on teeth in cleft areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 13 publications
2
32
3
14
Order By: Relevance
“…This difference in the prevalence of gingivitis of Cleft Lip patients among present study was lower than the study by Magdarena Stec-Slonicz et al, [12] due to better oral hygiene of the population in the present study. The mean number of sextants coded for healthy and bleeding was found to be maximum among the patients with Cleft Palate and calculus was found to be maximum among the subjects with Cleft Lip Alveolus and Palate was found to be not statistically significant.…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…This difference in the prevalence of gingivitis of Cleft Lip patients among present study was lower than the study by Magdarena Stec-Slonicz et al, [12] due to better oral hygiene of the population in the present study. The mean number of sextants coded for healthy and bleeding was found to be maximum among the patients with Cleft Palate and calculus was found to be maximum among the subjects with Cleft Lip Alveolus and Palate was found to be not statistically significant.…”
Section: Resultscontrasting
confidence: 83%
“…In the present study gingival bleeding was observed in 15.4% in Cleft Lip, 23% in Cleft Palate whereas in a study by Magdarena Stec-Slonicz et al, [12] in German population 53% in Cleft Lip and 13% in Cleft Palate. This difference in the prevalence of gingivitis of Cleft Lip patients among present study was lower than the study by Magdarena Stec-Slonicz et al, [12] due to better oral hygiene of the population in the present study.…”
Section: Resultscontrasting
confidence: 48%
See 2 more Smart Citations
“…4,5 Reductions in bone levels in the areas adjacent to the cleft region are associated with delayed tooth formation and eruption, anatomical defects, and problems with orthodontic movement. 6 Today, one of the best ways of imaging the alveolar bone is cone beam computed tomography (CBCT). Several advantages of this technique have been reported, such as its ability to evaluate the actual anatomy without superimposition of neighboring tissues and reduced radiation doses and costs compared with conventional CT. 7,8 Visualizing dehiscences and fenestrations is not possible with traditional two-dimensional (2-D) radiographs because of superimposition.…”
Section: Introductionmentioning
confidence: 99%